Social media in travel, tourism and hospitality : - Sigala, Marianna (Ashgate Pub., 2012)
Presenting cutting-edge theory, research and case studies investigating the web 2.0 applications and tools that transform the role and behaviour of the new generation of travelers, this book also examine the ways in which firms reengineer and implement their business models and operations.